PENGARUH ISLAMIC HUMAN CAPITAL MANAGEMENT DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BANK SYARIAH INDONESIA - Mallapiseng, Alif Fadil; Arifin, M. Rahmawan (POLITEKNIK LP3I JAKARTA, 2026)
Bank Syariah Indonesia has a limited number of human resources who possess adequate basic knowledge of the sharia context in banking. On average, the educational background of employees does not come from Islamic banking or related fields, but rather from conventional and general economics. In Islamic Human Capital Management (IHCM), the implementation of Islamic principles in human resource management is not only oriented toward improving employee performance but also contributes to employee job satisfaction. Therefore, this study is interesting and aims to examine whether IHCM and job satisfaction influence employee performance. This study employs a quantitative research design using the total sampling method, in which all members of the population are taken as research samples, totaling 40 respondents. Data were collected using a Likert scale supported by questionnaire (survey) techniques, observation, and a combination of both. Data analysis was conducted using SPSS version 22. The results of data analysis indicate that the Islamic Human Capital Management variable obtained a p-value (sig) of 0.000 < α (0.05), thus H₀ is rejected and H₁ is accepted. This finding concludes that IHCM has a positive and significant effect on employee performance. The job satisfaction variable obtained a p-value (sig) of 0.001 < α (0.05), thus H₀ is rejected and H₁ is accepted, indicating that job satisfaction has a positive and significant effect on employee performance. Simultaneously, the IHCM and job satisfaction variables obtained a p-value (sig) of 0.000 < α (0.05), thus H₀ is rejected and H₁ is accepted. Therefore, it can be concluded that IHCM and job satisfaction jointly have a significant effect on employee performance at Bank Syariah Indonesia KCP Kolaka.